Development of Christian Religious Education Learning Innovations Through the Implementation of the C3ME Model Academic Supervision - Harefa, Senida; Aritonang, Oktober Tua; Sitio, Robert Juni Tua (the International Journal of Education, Theology, and Humanities, 2024)
This research explores the idea that the C3ME model of academic supervision can help teachers increase their potential to develop learning innovations. It was concluded that the implementation of academic supervision plays an important role in improving the performance of Christian Religious Education teachers. The stages of the C3ME academic supervision model have a major impact on student learning progress. Through the application of the C3ME model, teachers can explore and increase the potential of teachers to develop their learning innovations. Model stages C3ME guides supervisors in collecting and analyzing learning conditions and weaknesses, which then becomes the basis for providing coaching for teachers. By following systematic steps, Class Visits, Coaching, Commitment, Monitoring, and Evaluation supervision can have a positive impact on teacher development and student learning. With feedback and support, the entire education ecosystem can experience significant improvements.